Measuring livelihoods and environmental dependence : (Washington, DC, 2011)
This book describes how to do a better job when designing and implementing household and village surveys for quantitative assessment of rural livelihoods in developing countries. It covers the entire research process from planning to sharing research results. It draws on the experiences from a large global-comparative project, the Poverty Environment Network (PEN), to develop more robust and validated methods, enriched by numerous practical examples from the field. The book will provide an invaluable guide to methods and a practical handbook for students and professionals.